Radio frequency connector insertion loss measured from 300 KHz Until 8.5 GHz by using network analyzer and mechanical calibration kits - Tan, Ming Hui; Bani Hashim, Ahmad Yusairi; Salleh, Mohd Rizal (Taylor's University, 2019)
In the design stage, an RF connector defaulted as lossless in a complex working system. However, RF connectors exist in varying types and dimensions that are technically identified as a delay line. In the high precision and accuracy measurement test system, an RF connector itself is considered as the primary factor in determining the level of accuracy and overall performance. To increase the accuracy and performance of the test system, every RF connector in the test system required to perform appropriate calibration and compensate for the loss of the test system. The purpose of this work is to perform calibration at 3.5 mm or SMA types of RF connector by using the mechanical calibration kits with an 8.5 GHz network analyser. Also, this work showed the S12 and S21 techniques in measuring the RF connector loss against the frequency range from 300 KHz until 8.5 GHz and analysed the differences between both methods. The results suggest that the methods applied were found in-tolerance